PEMBATALAN SURAT KEPUTUSAN PEMBERHENTIAN DENGAN TIDAK HORMAT NOTARIS MELALUI PUTUSAN PENGADILAN TATA USAHA NEGARA: STUDI KASUS PUTUSAN PENGADILAN TATA USAHA NEGARA JAKARTA NOMOR: 235/G/2019/PTUN.KT - Aulia, Tyreska; Fendri, Azmi; Adelina Mannas, Yussy (Penerbit Lafadz Jaya, 2025)
Legal protection is the right of every citizen not to get arbitrary treatment by law. Notary is a public official who is authorized to make authentic deeds and other authorities as referred to in Article 15 of UUJN, is also a citizen who gets legal protection. Violation of the implementation of the Notary position is an action that is prohibited by the Notary. However, if a Notary receives a report of an alleged violation of the exercise of office, it should be examined and tried in accordance with the procedures stipulated in the laws and regulations. The problems in this research are 1). How is the regulation of dishonorable dismissal of Notary according to positive law in Indonesia? 2). How is the judge's consideration regarding the cancellation of the decision letter of dishonorable dismissal of a Notary (case study of the Jakarta State Administrative Court decision number: 235/G/2019/PTUN.KT). 3). What are the legal consequences of canceling the decision letter to dishonorably dismiss a Notary (case study of the Jakarta State Administrative Court decision number: 235/G/2019/PTUN.KT). The research method used is normative juridical. The results showed that 1). Notaries who are dishonorably dismissed without a tiered examination by the Notary Supervisory Council feel aggrieved and take legal action through the State Administrative Court. 2). The basis of the judge's consideration in canceling the decree of dishonorable dismissal of Notary because the panel of judges concluded that the Notary Supervisory Council violated the General Principles of Good Government. 3). The PTUN verdict that has canceled the Notary's Dismissal Decree does not mutatis mutandis restore the position of Notary to become active again, this is evidenced by the Notary's Legal Entity Administration System license which has not been opened since 2019 until this research is completed and there is no guarantee of legal protection for the Notary's reappointment process. This is actually very detrimental to the Notary because he is no longer active as a Notary and cannot make authentic deeds as the authority of the Notary regulated in Article 15 of the UUJN.